Developing a novel toffee-type soft candy process by sonocrystallization: A preliminary study - Kopuk, Berkay (2024)
This study aimed to evaluate the applicability of sonocrystallization, an innovative process, as a low-cost and time-efficient alternative for the crystallization of confectionery dough, which is a crucial step in the production of conventional toffee-type soft candy. In this regard, according to the design plan, sonocrystallization time and current were selected as independent variables. The samples (36 run) nucleated by sonocrystallization using the optimum conditions (1600 and 2400 mA, 20 min) were allowed to aging under different times (0, 2, 4, 6, 8, and 10 min) and temperatures (60, 65, and 70 °C) in order to determine crystal growth. According to the texture profile analysis results, all parameters except for cohesiveness were significantly affected by both the sonocrystallization and aging conditions (p < 0.05), and dramatically higher hardness values were obtained for samples sonocrystallized at 2400 mA. Micrographs showed the formation of a crystalline network with more crystals of smaller size, fragmentation of larger crystals, and a more homogenous crystallization, especially in the samples sonocrystallized at 2400 mA and allowed to aging at >65 °C for durations of >6 min. The targets of the study were achieved by subjecting the samples to sonocrystallization at 2400 mA and aging at 70 °C for 8 min for crystal growth.